MOBILE-BASED INTERACTIVE MATHEMATICS LEARNING APPLICATIONS TO IMPROVE STUDENTS' LEARNING ACHIEVEMENT AND LEARNING INDEPENDENCE - Trisnawati, Trisnawati; Ipnuwati, Sri; Hendrowati, Tri Yuni; Mandala, Sri Surya (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2022)
Mathematics is a subject which is usually considered difficult by some students, including elementary school students, junior high school students, and high school students. Mathematics aims to encourage students to be skilled in using mathematics and also for practical needs and solving problems in everyday life such as calculating, measurements and interpreting data on computers. Currently, the mathematics learning process still uses conventional methods and lacks innovation in the learning which is taught, which is more fixated on so many textbooks so that this makes it difficult for students to learn these lessons, and will have an impact on students' scores being low. Along with the development of technology, there is an increase in people using smart devices, such as cellphones and tablets, but many are only used to play games. With these problems, there are now many mobile learning applications (m-learning) which aim to help students in efficient and interesting learning. This study aims to design and create a mobile-based application for learning mathematics for 6th grade students of elementary school to help them learn math-related problems in an interesting way. This research produces an application with a user-friendly menu display, and is equipped with practice questions and scores, so that it has benefits for 6th grade students of elementary school in solving problems related to mathematics subjects.